2020
DOI: 10.1515/jcim-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Moroccan microalgae: Spirulina platensis as a potential source of natural antioxidants

Abstract: AbstractBackgroundEthanolic, aqueous and lipidic extracts of Spirulina platensis were evaluated for their bioactive substances (polyphenols and fatty acids) and antioxidant activities using two different assays diphenyl-1-picrylhydrazyl (DPPH) and azino-bis (ethylbenzthiazoline-6- sulfonicacid (ABTS)). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…An impaired antioxidant system increases oxidative stress and inflammatory cytokine production; hence, targeting and constructing a formula with antioxidant potential is highly needed [ 56 ]. The topical application of SPNP-gel showed the highest antioxidant capacity, among treatment groups, by upsurging Nrf-2/HO-1 protein expressions compared to normally healed rats, and this antioxidant power was well documented by previous studies [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 68%
“…An impaired antioxidant system increases oxidative stress and inflammatory cytokine production; hence, targeting and constructing a formula with antioxidant potential is highly needed [ 56 ]. The topical application of SPNP-gel showed the highest antioxidant capacity, among treatment groups, by upsurging Nrf-2/HO-1 protein expressions compared to normally healed rats, and this antioxidant power was well documented by previous studies [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 68%
“…Analysis of phenolic compounds in the EAF was performed with Agilent 1100 (Agilent technologies, Santa Clara, CA, USA) equipped with a ZORBAX Eclipse SB-C18 reversed-phase analytical column of 100 × 4 mm and 3.5 µm particle size [ 71 ]. Column temperature was kept constant at 48 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Spirulina preparation can improve the intestinal environment by promoting the growth of Lactobacillus, Bifidobacterium and other intestinal beneficial bacteria ( 2 ). Recently, studies on Spirulina have shown that Spirulina contains many phenolic compounds, which usually have high antioxidant activity ( 3 ). Estrada et al found that phycobiliprotein (PC) extracted from Spirulina also has good antioxidant activity ( 4 ).…”
Section: Introductionmentioning
confidence: 99%